A Design-Oriented Model for Transmission Loss Optimization in Marine DOCs - Jan Kašpar; Francesco Mauro; Marco Biot; Giovanni Rognoni; Giada Kyaw Oo D’Amore (Journal of Marine Science and Engineering)
The even more restrictive regulations imposed on chemical and acoustic emissions of ships necessitate the installation of after-treatment systems onboard. The spaces onboard are limited, and the Exhaust Gas Cleaning Systems (EGCSs) have big dimensions, so an appropriate integration and optimization of EGCSs allows to save space and comply with international regulations. Moreover, in the available literature, there is a lack of guidelines about the design of integrated EGCSs. This study aims to develop an ad hoc optimization methodology that uses combined Computational Fluid Dynamics (CFD)–Finite Element Method (FEM) simulations, surrogate models, and Genetic Algorithms to optimize the acoustic properties of EGCSs while considering the limits imposed by the efficiency of chemical reactions for the abatement of NOx and SOx. The developed methodology is applied to a Diesel Oxidation Catalyst (DOC), and the obtained results lead to a system that integrates the silencing effect into the DOC.